Association between physical activity and health-related quality of life among adults in China: the moderating role of age - Hao, Hongying; Yuan, Yemin; Li, Jie; Zhao, Dan; Li, Peilong; Sun, Jingjie; Zhou, Chengchao (Frontiers in Public Health, 2024)
The aim of the study was to examine the association between physical activity (PA) and health-related quality of life (HRQoL) among adults, and to explore the role of age in the association between PA and HRQOL in Shandong, China.We investigated the relationship between PA and HRQoL and examined the moderated role of age in this association among adults with different age groups and physical activity levels. Data were obtained from the sixth China National Health Services Survey conducted in Shandong province in 2018. The multi-stage stratified cluster random sampling method was used to selected respondents, with individuals aged 18 and above included in present study. The tool of assessing HRQoL was the three-level EuroQol Five Dimensions Questionnaire (EQ-5D-3L).The study found PA was significantly related to HRQOL (P<0.05). The interaction analysis indicated that the relationship between PA and HRQOL was significantly different across young, middle-aged and older adults (P<0.05). Older adults with the sufficient PA (Coefficient=0.090, 95%CI: [0.081, 0.100]) and active PA (Coefficient=0.057, 95%CI: [0.043, 0.072]) had significantly higher HRQOL of life compared with young and middle-aged groups.PA was positively associated with HRQoL among the adults. Age played a moderate role between the association between PA and HRQoL. PA guidelines should be targeted designed for adults with different age to improve HRQoL.